A Situational Method for Creating Shared Understanding on Requirements for an Enterprise Architecture - Nakakawa, Agnes; Van Bommel, Patrick; Proper, Erik H. A.; Mulder, Hans J. B. F. (International Journal of Cooperative Information Systems, 2018)
Lack of shared understanding among stakeholders is a commonly cited drawback in enterprise architecture development. Stakeholders need to have shared understanding of requirements and principles for an enterprise architecture, and the extent to which the resultant architecture addresses their concerns. However, existing approaches for enterprise architecture development lack adequate capabilities for managing aspects associated with creating shared understanding among stakeholders. Although such aspects can be largely managed by approaches for collaborative decision making and soft systems thinking, these approaches lack details on the enterprise architecture process and its products. Therefore, this paper explores ways of mutually diminishing these gaps through adopting situational method engineering, to guide the development of a situational method for enabling stakeholders to acquire shared understanding of requirements for an enterprise architecture. The situational method presented herein is a component of a broader method for supporting collaboration between stakeholders and architects during enterprise architecture creation. Although the latter was successfully evaluated in 6 enterprises, it exhibited highest performance scores in two enterprises after it was amended with the situational method. Therefore, this paper also presents key findings from evaluating the situational method in the two agencies that are located in Uganda.
Keywords: Requirements for Enterprise Architecture; Shared Understanding; Situational Method Engineering